Постановка задачі оптимізації геометричних параметрів зубчастих передач з опукло-вгнутим контактом - Устиненко, Олександр Віталійович; Протасов, Роман Васильович; Бондаренко, Олексій Вікторович (Дослідно-видавничий центр Наукового товариства імені Шевченка, 2017)
Increase of contact durability teeth and reduction of gears dimensions is the important direction of mechanical engineering. The evolute gearings with convex-concave contact allows improving these indicators. In order to choose the parameters of the evolute gearing that provide maximum contact strength or minimum relative sliding velocities, it is proposed to solve the problem of optimization the geometric parameters of the initial contour and Bobillier constructing.
Build of geometrical parameters optimization problem for gears with convex-concave contact
Keywords: знос зубців; радіус кривизни; зачеплення; чотириланковий шарнірно-важільний механізм